1986
DOI: 10.2527/jas1986.6261641x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Restriction of Dietary Energy Intake during the Prepubertal Period on Secretion of Luteinizing Hormone and Responsiveness of the Pituitary to Luteinizing Hormone-Releasing Hormone in Heifers

Abstract: The working hypothesis that a low plane of nutrition during the prepubertal period delays puberty in heifers by retarding the prepubertal increase in secretion of luteinizing hormone (LH) was investigated. Secretion of LH and the responsiveness of the pituitary to LH-releasing hormone (LHRH) were compared in heifers fed a growing diet (which allowed spontaneous occurrence of puberty; n = 12; control) or an energy deficient diet (which delayed puberty; n = 11; delayed) during the prepubertal period. The dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
16

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 6 publications
2
67
0
16
Order By: Relevance
“…Entretanto, a função reprodutiva é limitada em condições de restrição nutricional, como a observada neste trabalho. De acordo com Day et al (1986), a restrição do nível energético deprime o eixo hipófise-hipotalâmico, o que diminui a atividade ovariana. Desta maneira, supõe-se que até mesmo novilhas púberes diminuíram a atividade cíclica, o que proporcionou baixa TP para estas fêmeas.…”
Section: Resultsunclassified
“…Entretanto, a função reprodutiva é limitada em condições de restrição nutricional, como a observada neste trabalho. De acordo com Day et al (1986), a restrição do nível energético deprime o eixo hipófise-hipotalâmico, o que diminui a atividade ovariana. Desta maneira, supõe-se que até mesmo novilhas púberes diminuíram a atividade cíclica, o que proporcionou baixa TP para estas fêmeas.…”
Section: Resultsunclassified
“…Numerous studies have demonstrated a close association between body growth, nutritional status and the timing of puberty onset. In cattle [4,5], sheep [6,7] and rodents [8,9], energy deficiency retards growth and delays the onset of puberty. Several lines of evidence from earlier investigations…”
Section: Introductionmentioning
confidence: 99%
“…Changes in body condition, direction of body weight change and intake of dietary energy influence the duration of anoestrus after parturition (Wiltbank et al, 1962;Dunn & Kaltenbach, 1980) and during the prepubertal period in bovine females. Nutri¬ tionally induced anoestrus or a delay in the onset of puberty in heifers that results from feeding them diets with low energy content is mediated by a suppression of luteinizing hormone (LH) in the circulation (Imakawa et ai, 1986;Day et al, 1986).…”
Section: Introductionmentioning
confidence: 99%